Ethical Aspects of Exhumation and Reburial of Soldiers and Civilians - Victims of War Massacre and Post-war Repression - Kossowski, Maciej Dariusz (Sensus Historiae, 2021)
Taking up the subject of ethical aspects of exhumation and reburial of victims of armed conflicts and totalitarian crimes seems justified in view of an increasing number of accidental discoveries of human bone remains from the 20th century, and also as a result of planned searches, including those of a commercial nature. Moreover, it is purposeful and necessary due to the fact that exhumations are not always carried out by professionals. Methodological shortcomings resulting from an individual way of conducting work, including an attitude to ethics, occurred also in teams of specialists. The purpose of the publication is to draw attention to the necessity of due respect for human remains left from a living being, so as not to offend the honour of those who have passed away. The article presents examples of selected exhumations undertaken without the participation of archaeologists and anthropologists as well as of works carried out at the sites of mass graves by specialists. At the end of the paper, conclusions were made regarding an update of the work methodology.